2011
DOI: 10.1007/s11605-011-1481-2
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Innervation and Early Postoperative Ileus in Mice

Abstract: Vagal afferents mediate sensitivity to low-threshold distension and 5-HT during postoperative ileus but not to high-threshold distension and bradykinin. Vagal inhibition of the intestinal immune response is present at 9 h but not detectable earlier, i.e., at 3 h of postoperative ileus when spinal reflex inhibition may prevail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 25 publications
(40 reference statements)
4
21
1
Order By: Relevance
“…Kalff et al [8] demonstrated the increased mRNA and protein expression of intercellular adhesion molecule 1 (ICAM-1) and p-selectin in the intestinal muscularis of POI, and the introduction of ICAM-1 antibody may prevent the aggregation of monocytes and neutrophils in the intestinal muscularis and ameliorate the functional disorder of jejunum circular muscle during POI. In the previous work, we confirmed this inflammatory response in the intestinal muscularis, and showed elevated myeloperoxidase (MPO) activity indicating increased numbers of neutrophils during POI [9]. All of these studies explored the role of inflammatory responses in POI at its early stage, few hours after the surgical operations [10].…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Kalff et al [8] demonstrated the increased mRNA and protein expression of intercellular adhesion molecule 1 (ICAM-1) and p-selectin in the intestinal muscularis of POI, and the introduction of ICAM-1 antibody may prevent the aggregation of monocytes and neutrophils in the intestinal muscularis and ameliorate the functional disorder of jejunum circular muscle during POI. In the previous work, we confirmed this inflammatory response in the intestinal muscularis, and showed elevated myeloperoxidase (MPO) activity indicating increased numbers of neutrophils during POI [9]. All of these studies explored the role of inflammatory responses in POI at its early stage, few hours after the surgical operations [10].…”
Section: Introductionsupporting
confidence: 55%
“…Specifically, POI is characterized by infiltration of leukocytes in the gut wall 24 h after surgery, and the majority of these cells are macrophages [7], [10], [28]. In this study, the method we used to induce postoperative ileus in mice is by mechanical intestinal manipulation which is an extremely well-established model world-wide [9], [29], [30]. However, it needs to be controlled by group size and standardized use under defined circumstances, to avoid the variability in experimental groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these authors, unlike us, could not show increased myeloperoxidase-positive infiltrates in the unmanipulated colon (15). In contrast, Mueller et al could show that vagal inhibition of the intestinal immune response is present at 9 h but not detectable earlier after IM (56). All in all, although the improved gastrointestinal and CT might be explained by an altered immunological activity, our findings do not exclude the contribution of neuronal signals to the postoperative ileus (2,14,42).…”
Section: Discussioncontrasting
confidence: 99%